Análise da estabilidade do tornozelo em movimentos esportivos e o efeito da órtese semi-rígida - Milanezi, Fernanda Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The ankle stability is an essential requirement for proper performance of the movement, however there is still no consistent understanding of ankle stability in dynamic situations. Worldwide, there is an increase in sports practice, with this there is an increased occurrence of injuries, especially ankle sprains. After ankle sprain, many individuals continue to report a feeling of instability. This dysfunction is known as Functional Ankle Instability (FAI) and causes several changes in ankle function. One method that is prescribed for the prevention of ankle sprain is the use of bracing, but the mechanism of action of this device is still not well understood in dynamic situations such as walking, running, jumping and other athletic movements. Thus, the present study aims to analyze the stability of the ankle using biomechanical variables (EMG, kinematics, kinetics) in individuals with and without functional ankle instability during the realization of common sports movements with and without an orthosis. This study involved 24 female volunteers, recreational athletes, recruited from a university population, who were divided into two groups: control group and the group with IFT. The subjects performed a torque assessment in isokinetic tests with five concentric/concentric and concentric/eccentric contractions speed of 30 °/s in inversion and eversion and three isometric eversion and inversion. Furthermore, performed sense of force (without visual feedback) and torque steadiness (with visual feedback) inversion and eversion, in which contraction held for 15 seconds at 25 % and 50% of CVIM test. The volunteers also underwent the following sports movements: walking, running, vertical jump, side jump, lateral displacement and cutting with and without bracing, and they had five attempts for each sports movement with two minutes between each motion block. During sports movements collected kinematic, kinetic and electromyographic data were...

A estabilidade do tornozelo é um requisito essencial para um adequado desempenho do movimento, no entanto ainda não há um entendimento consistente sobre a estabilidade do tornozelo em situações dinâmicas. Em todo o mundo, há um aumento na prática de esportes, com isso, há um aumento na ocorrência de lesões, principalmente de entorses de tornozelo. Após a entorse do tornozelo, muitos indivíduos continuam a relatar uma sensação de instabilidade. Essa disfunção é conhecida como Instabilidade Funcional do Tornozelo (IFT) e causa diversas alterações na função do tornozelo. Um dos métodos que é prescrito para a prevenção de entorse de tornozelo é o uso de órtese, mas o mecanismo de atuação desse dispositivo ainda não é bem entendido em situações dinâmicas como andar, correr, saltar e em outros movimentos esportivos. Diante disso, o presente estudo tem como objetivo analisar a estabilidade do tornozelo por meio de variáveis biomecânicas (EMG, cinemática, cinética) em indivíduos com e sem instabilidade funcional do tornozelo durante a realização de movimentos esportivos comuns com e sem uso de órtese. Neste estudo participaram 24 voluntários do sexo feminino, atletas recreacionais, recrutadas em uma população universitária, que foram divididas em dois grupos: grupo controle e grupo com IFT. As voluntárias realizaram uma avaliação dinamométrica em testes isocinético com cinco contrações concêntrico/concêntrico e concêntrico/excêntrico a velocidade de 30°/s em inversão e eversão e três contrações isométricas de eversão e inversão. Além disso, realizaram teste de senso de força (sem feedback visual) e de flutuações do torque (com feedback visual) de inversão e eversão, na qual realizaram contração durante 15s a 25% e 50% da CVIM. As voluntárias também realizaram os seguintes movimentos esportivos: marcha, corrida, salto vertical, salto lateral, deslocamento lateral e mudança de...
Keywords: Cinesiology; Cinesiologia; Estabilidade; Biomecânica; Entorse; Lesões corporais; Órtese; Tornozelos